Imagining holiness : classic Hasidic tales in modern times - Lewis, Justin Jaron, 1961- (McGill-Queen's studies in the history of religion., 2009)
Hasidic tales are often read as charming expressions of Jewish spirituality. This title offers a radical reappraisal of how we think of Hasidic tales, calling into question received notions of authenticity. It focuses on the neglected Hasidic literature of the early 20th century - primarily the work of Israel Berger and Abraham Hayim Michelson.